The Influence Of Total Asset Turnover And Net Profit Margin On Return On Asset At PT. Unilever Indonesia Tbk Period 2014-2023 - Cahyani, Dewi; Dinantara, Mohamad Duddy (Doktoral Ilmu Manajemen, Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of total asset turnover and Net Profit Margin on Return On Asset at PT. Unilever Indonesia Tbk period 2013-2024. This type of research uses quantitative with an assosiative approach and secondary data in the form of the company’s annual financial statements. The data analysis used is multiple regression analysis, classical assumption test, hypothesis testing and coefficient of determination. Significant test include t test and f test. The result showed that Total Asset Turnover partially had a significant effect on Return On Asset with a tcount value of 26.635 > 2.3642 ttabel and a significance value of 0.000 2.3642 ttabel and a significance value of 0.000